Red de Centros Educativos y desequilibrios territoriales. El caso de Aragón - Escolano Utrilla, Severino; Ruiz Budría, Enrique; Climent López, Eugenio (Geographicalia, 2016)
In this paper, territorial organisation of educational services in Aragon is studied. This Spanish region is characterized by strong territorial imbalances, as indicated by areas with a very low population density, a feeble settlement network and a transport infrastructure of low density and capability. These imbalances make difficult to provide the educational services that citizens have the right to access in conditions of territorial equity and efficiency. In this context, the suitability of school network to territorial structure is analysed. The great majority of the private centres, according to demand criteria, are located in the urban settlements. Otherwise, the network of public centres reaches the most part of the territory.